Applying Problem Solving Approach in Teaching Addition and Subtraction Word Problems in Diverse Grade 3 Classrooms - Sambo, Tinyiko Florence; Makgakga, Tšhegofatšo Phuti (Research in Social Sciences and Technology, 2024)
Word problem solving is an approach that can increase knowledge, improve performance and develop learners’ critical thinking skills that can assist them in solving mathematical and real-life problems. This study examined the effectiveness of using a word problem solving approach to improve Grade 3 learners’ performance when learning addition and subtraction. The study employed this hypothesis to test the difference between the experimental and control groups and between the pre-test and post-test with learners in diverse classrooms solving addition and subtraction word problems. A pre-test-intervention-post-test research design was used to collect the data. Baseline lesson observations and unstructured interviews were conducted to understand the effectiveness of the problem solving approach in teaching number concepts, problems, addition and subtraction. The results of the study revealed a significant difference between the experimental and comparison groups when solving addition and subtraction word problems. Furthermore, there was a significant difference between the pre-test and the post-test in the experimental group. It was concluded that word problems could be taught by following steps for problem solving and equipping learners with essential reading skills to help them comprehend what they are reading. The interviews showed that teachers do not have enough time for learners who experience learning challenges and reading in particular in pursuit of covering the curriculum. Learners in the foundation phase must be taught money problems and problem-solving skills to acquire knowledge to be used in higher grades and real-life situations.